Potensi penggunaan sisa buangan cat industri automobil dalam penghasilan konkrit - Shahrom Md. Zain; Ng, Foo Sun; Roszilah Hamid (2006)
The objective of this study is to determine the effect of incorporating paint sludge bottom ash as cement replacement materials to the workability of fresh concrete and compressive strength of concrete. The paint sludge bottom ash is obtained from the incinerator plant of Perodua Manufacturing Sdn. Bhd, Sungai Choh, Rawang Selangor. Tests on the properties of the ash shows that the specific gravity is 2.50 and the specific surface of the ash particle is 829.82 cm2/g. The heavy metals test shows that the highest concentration of heavy metals is barium, which is 144.18 mg/L followed by zinc, 16.96 mg/L and lead, 15.72 mg/L. Meanwhile, the content of CaO and SiO2 found in the bottom ash are small. There are only 1.82% and 7.68% (weight in percent). The test on the properties of fresh concrete incorporating 10%, 20% and 40% of the paint sludge bottom ash by weight shows that the slump of the concrete increases as the bottom ash percentage increases. Consequently, test on strength shows that compressive strength decreases as the percentage of bottom ash replacing the amount of cement increases. The compressive strength (28th days) of the concrete incorporating 40% bottom ash experienced the maximum reduction (more than 50%) both for samples undergone wet or air-dry curing